Pemanfaatan limbah budidaya udang vannamei menjadi pupuk kompos di Gampong Ulee Pulo Kecamatan Dewantara Kabupaten Aceh Utara (The utilization of vannamei shrimp culture waste become compost fertilizer in Ulee Pulo Village, Dewantara Sub District North Aceh District) - Erniati, Erniati; Syahrial, Syahrial; Imamshadiqin, Imamshadiqin; Imanullah, Imanullah; Erlangga, Erlangga; 'Akla, Cut Meurah Nurul; Andika, Yudho; Irmayunita, Irmayunita; Handayani, Meutia; Mataniari, Azhari; Dila, Nuriana; Prasetyo, Repki (Buletin Pengabdian, 2022)
This community service aims to provide education and improve the skills of the residents of Ulee Pulo Village in making good use of vannamei shrimp waste. Service activities were carried out using the community development approach method through training based on theory and practice with lectures and focused discussion (focus group discussions). The results of the service were carried out well, structured, smoothly, and successfully involving the community directly, especially the wives of the aquaculture farmers of Gampong Ulee Pulo. The target achieved is that the participants already have the skills and practice the process of making compost independently. In conclusion, the community is skilled in making compost independently.